(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: To assess the quality of life of the elderly with cardiovascular diseases in Hanoi in 2022. Subjects and research methods: A cross-sectional study in the community. The research subjects are elderly people with cardiovascular diseases living in 5 wards in Dong Da district, Hanoi, from 4/2022-10/2022. Results: Compared to the quality of life of older adults aged 65 years in the general population (0,89), the elderly with cardiovascular diseases had a significantly lower quality of life (0, 7176), in which anxiety/melancholy and pain/discomfort are the factors affecting the quality of life the most. On the other hand, cardiovascular diseases with more symptoms and a greater burden of symptoms, such as cerebrovascular disease, arrhythmia, heart failure, etc., have a lower quality of life than other cardiovascular diseases. Besides, not only demographic characteristics such as age, sex, education levels, and other pathological characteristics but also economic, cultural, marital, and social characteristics also affect the quality of life of the elderly with cardiovascular diseases. Conclusion: Research has shown the understanding of factors affecting the quality of life (physical, emotional, and social life) of patients with cardiovascular diseases, from which giving appropriate interventions and treatments.